High temperature steam oxidation of chromium-coated zirconium-based alloys: Kinetics and process. (1st May 2020) - Brachet, Jean-Christophe; Rouesne, Elodie; Ribis, Joël; Guilbert, Thomas; Urvoy, Stéphane; Nony, Guillaume; Toffolon-Masclet, Caroline; Le Saux, Matthieu; Chaabane, Nihed; Palancher, Hervé; David, Amandine; Bischoff, Jérémy; et al.
Highlights: Oxidation of Cr-coated Zr alloys is studied under steam up to 1500 °C. Oxidation kinetics vary depending on the actual protectiveness of the Cr coating. Different underlying diffusion mechanisms are highlighted. Cr volatilization appears to be negligible. Effect of Zr-Cr eutectic beyond 1300 °C is studied. Abstract: The oxidation of chromium-coated zirconium-based alloys is studied under steam at temperatures ranging from 800 °C up to 1500 °C and for oxidation times ranging from a few minutes up to a few hours. For oxidation temperatures up to 1300 °C, the overall oxidation kinetics is nearly parabolic at the beginning of oxidation, when the Cr outer layer is protective. Finally, it significantly accelerates and hydrogen is absorbed during a short period. These steps correspond to different oxidation and diffusion mechanisms, involving: growth of outer chromia scale; Zr-Cr interdiffusion, inducing Zr(Cr, Fe)2 intermetallic layer thickening then disappearance due to transformation into metallic chromium and zirconia; transport of oxygen through residual chromium (in particular along grain boundaries) and into the zirconium substrate, and finally growth of a sub-coating zirconia. The additional effect of the Zr-Cr eutectic reaction occurring when the oxidation temperature is increased beyond 1300 °C is also studied and briefly discussed.